2013
DOI: 10.1177/1012690213515664
|View full text |Cite
|
Sign up to set email alerts
|

Drinking with the derby girls: Exploring the hidden ethnography in research of women’s flat track roller derby

Abstract: This paper explores Blackman's concept of 'hidden ethnography' with respect to drinking alcohol by and with participants during ethnographic research of a women's flat track roller derby league. A brief review of the positive and negative consequences of drinking alcohol for the research process pays specific attention to the potential consequences for research participants and the researcher. Following this, the researcher reveals elements of the hidden ethnography of this project, and explores how drinking b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, the tide is turning with the emergence of ‘hidden ethnographies’ where researchers talk about aspects of their research that might otherwise go unpublished because content is deemed too emotive or controversial (Blackman, 2007). Recent examples include discussions of the ethical dimensions of researchers’ guilt and privilege (DeLuca and Maddox, 2015); use of field diaries (Punch, 2012); disclosure of personal information (Harris, 2015); changing personas over the course of fieldwork (Purdy and Jones, 2013); and drinking alcohol with research participants (Donnelly, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the tide is turning with the emergence of ‘hidden ethnographies’ where researchers talk about aspects of their research that might otherwise go unpublished because content is deemed too emotive or controversial (Blackman, 2007). Recent examples include discussions of the ethical dimensions of researchers’ guilt and privilege (DeLuca and Maddox, 2015); use of field diaries (Punch, 2012); disclosure of personal information (Harris, 2015); changing personas over the course of fieldwork (Purdy and Jones, 2013); and drinking alcohol with research participants (Donnelly, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Like Thorpe’s (2012) analysis of après snow culture and Donnelly’s (2013) analysis of roller derby participants, my analysis suggested that tournament parties, and their associated drinking, form an important part of what it means to be an Ultimate player. Gerald, for example, recalled his first tournament in this way:Afterwards we went to the student bar and met all the other teams and socialized and I hadn’t really done that with other sports….…”
Section: Methodsmentioning
confidence: 93%
“…It was a good introduction [to Ultimate], I think’. Much like the roller derby participants Donnelly (2013) studied, many teams aim to ‘win the party’, by being the last team remaining on the dance floor, while tournaments often offer prizes to the players with the best costume at the party. The recognition of the importance of the party, of drinking and socializing with other players, points towards Ultimate’s lifestyle being one of calculated, hedonistic indulgence.…”
Section: Methodsmentioning
confidence: 99%
“…To this, we would add anthropological studies of play and games. Ethnographies in this vein have addressed questions pertaining to who has the power to participate in sport (e.g., Donnelly, 2014;Laurendeau, 2011;Maddox, 2015), how sport is a site for the tactical (re)production of normative identities (e.g., De Luca, 2013; Francombe, Rich, & De Pian, 2014;Swanson, 2009), how sport involvement jibes with dominant cultural worldviews (e.g., Atkinson, 2009;Fletcher, 2014), and how the construction of privileging social and cultural networks are reinforced through participation (e.g., Olive & Thorpe, 2011;Walton & Fisette, 2013). Importantly, as PCS scholars note, such developments are by no means new.…”
Section: Pcs and (Re)consideration Of Ethnography: Promises And Pitfallsmentioning
confidence: 99%